DYNAMICS AND CHANGES OF SOCIAL STRATIFICATION OF THE SASAK ROYAL 1970-2000 - Lalu Murdi; Jujuk Ferdianto; Bambang Eka Saputra (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2020)
This research aims to uncover and analyze the form of socialstratification in sasak noble people in Jerowaru Sub-District of East Lombok Regency-NTB between the 1970s and 2000s. The research approach used is qualitative research with historical methods where in addition to obtaining the source of documents as well as using oral sources to be able to perform reconstruction. The results showed that before the 1970s the existence of social stratification in the community in Jerowaru Village in particular had quite high differences both from aspects of language, customary clothing, marriage system and others.  Sehas in the 1970s has shown a change, this is not separated from the influence and existenceof pesantran hut established by one of the famous religious figures in Lombok namely Tuan Guru Mutawalli, and at the same time some fundamental changes caused by intenal aspects. One interesting thing about the cultural history of the existence of nobles in the period between 1970-2000 is that there was a very rapid change, because some other studies showed that the change in the form of social stratification elsewhere, especially the nobles showed a changethat was not very significant.